THE MEANING OF INTERCULTURAL COMMUNICATION - Eilers, Franz Josef (Journal of Dharma, 1999)
Communicating between cultures becomes more and more important in a rapidly shrinking world. Thus intercultural communication as the study of communication and interaction between members from different cultures has developed into a special field of studies. A growing number of publications testifies to this (e.g. Wiseman, Rogers and Steinfatt, Jandt).